Evaluation of a Bacterial Single-Cell Protein in Compound Diets for Rainbow Trout (Oncorhynchus mykiss) Fry as an Alternative Protein Source - Abbas Zamani; Maryam Khajavi; Masoumeh Haghbin Nazarpak; Enric Gisbert (Animals, 2020)
A 60-day trial was conducted in rainbow trout (Oncorhynchus mykiss) fry (initial weight = 2.5 ± 0.6 g) to evaluate the potential use of a bacterial single-cell protein (SCP) as an alternative protein source. Five experimental diets with different levels of fishmeal replacement (0, 25, 50, 75 and 100%) and no amino acid supplementation were tested. At the end of the trial, we found that fry fed diets, replacing 25 and 50% of fishmeal with bacterial SCP, were 9.1 and 21.8% heavier, respectively, than those fed the control diet (p < 0.05), while Feed Conversion Ratio (FCR) values were also lower in comparison to the reference group. These results were also supported by Protein Efficiency Ratio (PER) and Lipid Efficiency Ratio (LER) values that improved in fish fed diets replacing 50% fishmeal by bacterial SCP. The inclusion of SCP enhanced Feed intake (FI) (p < 0.05), although FI was reduced at higher inclusion levels (>50%), which was associated to feed palatability. High levels of bacterial SCP (>50%) affected the muscular amino acid and fatty acid profiles, imbalances that were associated to their dietary content. The broken-line regression analysis using muscle DHA content and weight gain data showed that the maximum levels of fishmeal replacement by bacterial SCP were 46.9 and 52%, respectively.